Media in china: features of functioning - Kosiuk, Oksana M. (European Open Science Space, 2025)
The article also states that the status of Uyghur journalists in China is the same as that of Kurds in Iraq, Iran, Syria, Turkey and Afghanistan. Media professionals from Hong Kong and Taiwan should also be considered less status and, accordingly, more controlled. They are the target of the ‘watchful eye’ of censorship. However, for some reason, almost all of the accusations relate mainly to business activities, social issues, personal positions and migration policy rather than journalism itself. It has been determined that sensitive topics such as Covid-19, anti-sexual violence movements, etc. are also the reason for bans. It was found out that Chinese media have recently attracted the interest of scholars as well. Following the numerous discussions, a number of recommendations were made that will contribute to a better understanding of Chinese journalism and the establishment of international contacts.
Keywords: journalism; Chinese media; Ukraine; fact